Some lifestyle habits of female Belgrade university students with migraine and non-migraine primary headache - Vlajinac, Hristina (Springer-Verlag, 2003)
We performed a prevalence study to compare some lifestyle habits between subjects with migraine and those with nonmigraine primary headaches. We surveyed female students in randomly selected classes of the School of Medicine and the School of Pharmacy, Belgrade University. Among all observed students (1943 subjects), 245 had migraine and 1053 had non-migraine primary headache. According to multivariate logistic regression analysis, the following factors were associated with migraine: irregular eating (odds ratio (OR)=1.99; 95% confidence interval (95% CI), 1.69 to 2.34; p<0.01), sleep duration shorter than usual (OR=1.18; 95% CI 1.00 to 1.38; p=0.0449) and smoking >10 cigarettes per day (OR=1.18; 95% CI=1.00 to 1.39; p=0.0433). The results of the present study are in line with some other investigations suggesting that some lifestyle habits probably play a role as migraine precipitants.